Utility of Blood Markers for Predicting Outcomes of Fertility Preservation in Patients With Breast Cancer - Hong, Yeon Hee; Kim, Seul Ki; Lee, Jung Ryeol; Suh, Chang Suk (Frontiers in Endocrinology, 2022)
This study was to investigate the usability of blood markers for predicting controlled ovarian stimulation (COS) outcomes in patients with breast cancer undergoing fertility preservation (FP). In total, 91 patients with breast cancer who underwent COS using a letrozole-combined gonadotropin-releasing hormone (GnRH) antagonist protocol before chemotherapy were enrolled retrospectively in a single tertiary hospital. FP outcomes were compared in relation to the mean platelet volume (MPV), MPV/platelet count (PC), neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and lymphocyte-to-monocyte ratio (LMR). The cutoff values for obtaining 10 or more mature oocytes as favorable prognoses were obtained for each parameter, and the COS outcomes were compared based on the cutoff values. The optimal cutoff levels for MPV and MPV/PC were 10.15 (sensitivity: 90.0%; specificity: 45.1%; AUC: 0.687; 95% CI [0.563, 0.810]) and 0.41 (sensitivity: 65.0%; specificity: 67.6%; AUC: 0.682; 95% CI [0.568, 0.796]), respectively. The oocyte numbers did not significantly differ in relation to the cutoff values of NLR, PLR, and LMR (p > 0.05). However, the total numbers of acquired and matured oocytes were significantly lower in the group with MPV<10.15 than in those with MPV≥10.15 (8.0±5.1 vs. 12.6±9.1, p=0.003; 4.0±3.7 vs. 7.3±6.3, p=0.002, respectively). Similarly, considering the cutoff MPV/PC of 0.41, the low MPV/PC group showed a significantly lower total oocyte yield than the high MPV/PC group (9.5±7.1 vs. 13.1±9.1, p=0.048), while the number of mature oocytes showed similar patterns with no statistical significance (5.3±5.4 vs. 7.3±6.1, p=0.092). By logistic regression analysis, Age, AMH and MPV, MPV/PC≥0.41 were significant factors for acquisition of 10 or more MII oocytes (p=0.049, OR: 0.850; p<0.001, OR: 1.622; p=0.018, OR: 3.184; p=0.013, OR: 9.251, respectively). MPV or MPV/PC can be reliable markers for predicting FP outcomes in patients with breast cancer. Protocols to acquire more oocytes, such as the dual-trigger approach, could be recommended for patients with breast cancer with MPV<10.15. Furthermore, a higher dose of gonadotropins was considered to obtain more oocytes in patients with MPV/PC<0.41.